Evaluation of early anatomical changes following canaloplasty with anterior segment spectral‐domain optical coherence tomography and ultrasound biomicroscopy. (9th December 2015) - Fuest, Matthias; Kuerten, David; Koch, Eva; Becker, Jakob; Hirsch, Thalia; Walter, Peter; Plange, Niklas
Abstract: Purpose: To analyse structural changes in conjunctiva, sclera and Schlemm's canal (SC) following canaloplasty with optical coherence tomography (AS‐OCT) and ultrasound biomicroscopy (UBM). Methods: Fifteen patients undergoing canaloplasty were included in this prospective study. AS‐OCT images were acquired pre‐ and 1, 7, 30 and 90 days postoperatively. UBM was performed 3 months postoperatively. The surgical site was evaluated for the presence of SC, transscleral filtration, a scleral lake and the visibility of intra‐Schlemm‐sutures. The height and width of SC were measured at the 3 and 9 o'clock limbus position. Results: After canaloplasty, SC was detectable with AS‐OCT in 93% of the patients on day 1. The increase in height was higher than that in width (height: +369%, p  =  0.0004, width: +152%, p  =  0.002). IOP was negatively correlated to SC's width 1 week postoperatively ( r =  −0.63, p  =  0.04) and to SC's height until 3 months ( r =  −0.66, p  =  0.02) postoperatively. Using UBM, a reflection of the traction sutures indicated SC's position in all patients. Transscleral filtration was found in all patients using AS‐OCT, demonstrating a peak 1 week postoperatively. At 3 months, a scleral lake could be visualized in 50% and 83% of patients using AS‐OCT and UBM, respectively. Conclusions: AS‐OCT offers a high resolution for imaging superficial conjunctival areas and SC after canaloplasty, whereas UBM is capable of detecting deeper structures such as scleral lakes or intra‐canal‐sutures. The results imply a correlation of the dilation of SC with the IOP‐lowering effect and an early pronounced transscleral filtration following canaloplasty.